PENGARUH REKRUTMEN, PENGEMBANGAN, PENILAIAN TERHADAP KINERJA GURU DAN KARYAWAN DI SLB NEGERI 1 GUNUNGKIDUL - Magdalena Bendot Ratu Langit; Muhammad Robi Nurwahyudi (MANAJEMEN DEWANTARA, 2026)
This study aims to analyze the effect of recruitment, development, and performance appraisal on the performance of teachers and staff at SLB Negeri 1 Gunungkidul. The research employed a quantitative approach using a survey method through Likert-scale questionnaires distributed to 55 teacher and staff respondents. Data were analyzed using multiple linear regression, including t-test, F-test, and coefficient of determination (R Square), with the assistance of IBM SPSS version 27. The results indicate that recruitment has a negative and insignificant effect on teachers’ and staff performance. In contrast, development and performance appraisal have a positive and significant effect on performance. Simultaneously, recruitment, development, and performance appraisal significantly affect teachers’ and staff performance. The coefficient of determination (R²) of 0.706 indicates that 70.6% of teachers’ and staff performance can be explained by the three variables, while the remaining 29.4% is influenced by other factors outside this study. Keywords: recruitment, development, performance appraisal, teachers and staff performance.